The Issues of Artistic Psychology in Jane Austen’s “Pride And Prejudice” (Eurasian Research Bulletin, 2023)
This article outlines the importance of Jane Austen's life and her legacy in world literature. Jane's parents were very book-loving and enlightened people, the writer’s curiosity in writing fiction was appeared in her early age. Jane Austen (1775 - 1817) is an English author who reflected the reality of middle-class women at the beginning of the 19th century. This article is about one of Jane Austen's famous works called "Pride and Prejudice".